2019
DOI: 10.1111/cen.14124
|View full text |Cite
|
Sign up to set email alerts
|

Basal serum luteinising hormone cut‐off, and its utility and cost‐effectiveness for aiding the diagnosis of the onset of puberty in girls with early stages of breast development

Abstract: Objective To determine basal and gonadotrophin‐releasing hormone analogue (GnRHa)‐stimulated peak luteinising hormone (LH) cut‐offs to diagnose onset of early or normal puberty in girls with each Tanner stage of breast (II and III). Design, Patients and Measurements A retrospective study of 601 girls with breast onset before 8 years of age who underwent GnRHa test was conducted. Patients were categorized as CPP and premature thelarche. Each group was divided into two subgroups; Tanner II and III. Cost‐effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…However, based on the minimum baseline values of the group with CPP, an overlap of these data was observed, indicating the uncertainty of these values in girls, as a way to differentiate CPP from PT as previously demonstrated in the literature [11,12]. We agree, however, that baseline values above 0.6-1.0 could dispense the test [11,[27][28][29][30].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…However, based on the minimum baseline values of the group with CPP, an overlap of these data was observed, indicating the uncertainty of these values in girls, as a way to differentiate CPP from PT as previously demonstrated in the literature [11,12]. We agree, however, that baseline values above 0.6-1.0 could dispense the test [11,[27][28][29][30].…”
Section: Discussionsupporting
confidence: 74%
“…The analysis of the ROC curve showed cutoffs of 0.10 IU/L for baseline LH, 0.16 for baseline LH/FSH ratio, and 13.3 pg/mL for estradiol with sensitivity and specificity profiles shown in Table 3. Some authors have reported similar values and suggested that the baseline LH values are sufficient to demonstrate the activation of the HPG axis [29,30]. However, based on the minimum baseline values of the group with CPP, an overlap of these data was observed, indicating the uncertainty of these values in girls, as a way to differentiate CPP from PT as previously demonstrated in the literature [11,12].…”
Section: Discussionsupporting
confidence: 55%
“…Distinct cut-off values for boys and girls are rarely reported (Table 4). Neely et al [43] found the same cut-off values in both the sexes, while Brito et al [41] indicated a higher cut-off in boys in comparison with girls. Resende et al [45] reported a higher cut-off in girls than in boys by using an IFMA method as in Brito et al [41], while they found the contrary with an ICMA assay [45] (Table 4).…”
Section: Laboratory Assessmentmentioning
confidence: 92%
“…[19][20][21][22][23][24][25][26][27][28] A recent study in 2020 by Wankanit et al suggested a cut-off basal LH level of 0.2 IU/L for CPP diagnosis with a sensitivity and specificity of 90.0-95.0%. 29 Brain pathology has been identified in 5.0-15.0% of CPP girls and 50.0-100% of CPP boys. The most common brain pathology is a hypothalamic hamartoma.…”
Section: Diagnosis and Laboratory Testsmentioning
confidence: 99%